Protective acquired immunity to Enteromyxum scophthalmi (Myxozoa) is related to specific antibodies in Psetta maxima (L.) (Teleostei) - Sitjà-Bobadilla, Ariadna; Palenzuela, Oswaldo; Riaza, Ana; Macías, M. A.; Álvarez-Pellitero, Mª del Pilar (Scandinavian Journal of Immunology, 2007)
The acquired protection of three groups of turbot that had survived enteromyxosis outbreaks was tested by challenging with E. scophthalmi in three different experiments. The relation of such a response with the kinetics and duration of antibody production (determined by an ELISA) was studied. The progression of the infection was evaluated by PCR. In experiments 1 and 2, in which turbot had cohabited with highly infected fish during outbreaks, parasite prevalence and mortality were very low or null, and there was a progressive and statistically significant increase in the mean antibody production up to 350 and 152 days post-exposure respectively. By contrast, in experiment 3, fish (coming from non-infected tanks during the initial outbreak), both infection prevalence and cumulative mortality reached 92.8%, and specific antibodies were detected only in two fish. The observed differences in mortality after challenge appear to be related to the production of specific antibodies and it is probably accompanied by a repertoire of mechanisms of innate immunity. The exploitation of the immune system through breeding selection programmes as a possible strategy to control the disease is discussed. Funding for this study was provided by Stolt Sea Farm S. A. through a research contract. Additional support was obtained from the EU, the Spanish Ministerio de Ciencia y Tecnología and the Xunta de Galicia (research grants FEDER 1FD97-0679-C02-01, AGL2001-2241-C02-01 and PGITDIT-02RMA-25E). We are grateful to Ma Angeles Gonzalez, Ma Luisa Alonso and Ma Carmen Ballester for technical support in PCR assays and ELISA.